2020
DOI: 10.34001/edulingua.v7i1.1167
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Corrective Feedback on Academic Writing Performance: Efl Students’ Perceptions

Abstract: In the context of higher education, corrective feedback plays a crucial part in academic writing. This paper, therefore, aims to explore the role of corrective feedback on the academic writing performance of EFL students at State Islamic Institute of Kudus. The study employed a qualitative research. In order to gather data, the writer interviewed the students about the perception of the use corrective feedback in enhancing their performance in academic writing. In addition, observation and documentation were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…On the other hand, the two-way method was used when the teacher expected to have an online discussion, feedback, and evaluation using google meet or other platforms. As strengthened by (Wahyuningsih, 2020), providing feedback and evaluation are badly needed to promote students' comprehension of language skills. By combining the two methods in the EFL classroom, students would be more motivated to learn English and develop their ideas through discussion (Hrastinski, 2014).…”
Section: The Implementation Stage Of E-learningmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the two-way method was used when the teacher expected to have an online discussion, feedback, and evaluation using google meet or other platforms. As strengthened by (Wahyuningsih, 2020), providing feedback and evaluation are badly needed to promote students' comprehension of language skills. By combining the two methods in the EFL classroom, students would be more motivated to learn English and develop their ideas through discussion (Hrastinski, 2014).…”
Section: The Implementation Stage Of E-learningmentioning
confidence: 99%
“…Meanwhile, in written forms, the language teacher has written some feedback in WhatsApp group or google classroom. Giving feedback is essential to reinforce students' achievement in English skills (Suchona & Shorna, 2019;Wahyuningsih, 2020;Zhai & Gao, 2018).…”
Section: Figure 2 Form Of Assessmentmentioning
confidence: 99%
“…In the context of learning to write, corrective feedback helps students identify errors they make in their writing (Wahyuningsih, 2020). With given feedback, students receive clearer understanding of their learning curve as a basis to develop the capacity to implement acquired skills in future writing situations (Strobl, 2014;Wong et al, 2017), and in turn improve the quality of texts they produce (Crinon & Marin, 2010).…”
Section: The Role Of Teachers' Feedback In Developing Students' Writing Skillsmentioning
confidence: 99%
“…One of the challenges of academic writing that mostly found by EFL students is academic convention (Abbas et al, 2020;Wahyuningsih, 2020aWahyuningsih, , 2018b. Other challenges that may become major obstacle are the difficulties of making claims and strong arguments, lack of appropriate and numerous vocabularies, and the limited style of writing.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding academic writing studies, many studies have reported that the importance of academic writing in several setting and disciplines. In addition, some studies highlight numerous problems found by EFL students in academic writing including lack of appropriate structure and English vocabularies, lack of organizing ideas, lack of delivering arguments, lack of criticizing issues (Wahyuningsih, 2018a(Wahyuningsih, , 2020a(Wahyuningsih, , 2020b(Wahyuningsih, , 2018b. However, few studies reported the problems of using appropriate English phrases in academic writing.…”
Section: Introductionmentioning
confidence: 99%